(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2026)
This study explores the role of cultural heritage in the development of tourism in Uzbekistan. Uzbekistan’s rich historical and cultural assets, including historic cities, architectural monuments, traditional crafts, and festivals, attract both domestic and international tourists. The study uses secondary data from government reports, UNESCO and UNWTO publications, and academic sources. Findings show that heritage tourism contributes to economic growth, employment, and regional development while preserving tangible and intangible cultural assets. Sustainable management, community involvement, and strategic promotion are essential to maintain these benefits. Cultural heritage remains a key pillar for tourism development in Uzbekistan, supporting long-term socio-economic growth and national identity.